Restorative justice: theoretical foundations - Weitekamp, Elmar G. M.; Kerner, Hans-Jürgen (Willan Pub, 2010)
This title explores the theoretical foundations of restorative justice. It looks at restorative justice philosophy and the ways in which models have been applied to adults, corporate crime, family violence and to cases of extreme violence